Guide to antimicrobial therapy 2017 - Chan, Louisa; Mat Nor, Mohd Basri; Ibrahim, Noor Airini; Tai, Li Ling; Tay, Charlene; Teh, Kimberly Hwei Lin (Malaysian Society of Intensive Care and Ministry of Health Malaysia, 2017)
Sepsis still remains the leading cause of admissions and deaths in the ICU. The administration of antibiotics is imperative in its treatment. Like many areas of medicine the knowledge of sepsis and antibiotic use has markedly increased especially the later in areas of pharmacokinetics and pharmacodynamics. It becomes urgent to continually evaluate and apply this knowledge, hence the need to revise this antimicrobial guide after 5 years. The threat that one day antibiotics may be obsolete is not a fallacy. Often we are oblivious to the fact that we, the prescribers play a significant role in the propagation of resistant organisms through poor prescribing habits. Antibiotic stewardship calls for a multidisciplinary approach to the handling of antibiotics. A chapter has been dedicated to this. The book remains true to its aims as a convenient up-to-date pocket guide for local doctors caring for the critically ill septic patient. However it must be emphasised that the recommendations do not over ride sound clinical judgement and local antibiotic-susceptibility data. We would like to thank our reviewers for their expertise and invaluable recommendations. This book has been a culmination of many hours of evidence review and exchange of opinions. We hope it will be a useful compendium for daily practice.